HUBUNGAN WORK LIFE BALANCE DENGAN KEPUASAN KERJA PADA GURU DI SMK KABUPATEN PATI - Ellyda Yohan Pranindhita Pranindhita; Doddy Hendro Wibowo (Universitas Negeri Medan, 2020)
This study aims to determine the relationship between work life balance and job satisfaction. This study uses a correlational quantitative method. The number of participants in this study were 36 female teachers who were married. The technique used was the saturated technique all members of the population were used as samples. The research data was taken from SMK in Pati Regency. Data used for the work life balance scale from Fisher, Bulger and Smith (2009) and the Job Satisfaction Scale use the Job Satisfaction Survey Scale from Spector (1997). Data analysis using Pearson Product Moment correlation using SPSS for windows version 16.0. The results of this study there is no relationship between work life balance and job satisfaction (r = -0.035). This shows that job satisfaction of married female teachers is not affected by work life balance.Keywords : Work Life Balance, Job Satisfaction.